Krvoločni osvajalci in hudičevi vojaki - Mlakar, Anja (Studia mythologica Slavica, 2014)
This paper presents and compares the image of "the barbaric Turk" in the political-ideological discourses and the perception of "the Turk" as a dangerous, cosmos-disturbing foreigner in Slovene folklore. The centuries-old concept of "the barbarian", ideological propaganda and the archaic fear of thereatening outsider in traditional culture all contributed in the process formation of a certain imagery of "the Turk".
Keywords: ethnology; etnologija; folk legends; ljudske legende; Slovene folk tales; slovenske ljudske pripovedke; osvajalci; barbari; Turki